2019
DOI: 10.1103/physrevx.9.021024
|View full text |Cite
|
Sign up to set email alerts
|

Free and Bound States of Ions in Ionic Liquids, Conductivity, and Underscreening Paradox

Abstract: Using molecular dynamics simulations and theoretical analysis of velocity-autocorrelation functions, we study ion transport mechanisms in typical room-temperature ionic liquids. We show that ions may reside in two states: free and bound with an interstate exchange. We investigate quantitatively the exchange process and reveal new qualitative features of this process. To this end, we propose a dynamic criterion for free and bound ions based on the ion trajectory density and demonstrate that this criterion is co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(154 citation statements)
references
References 99 publications
9
145
0
Order By: Relevance
“…Further investigations on the temperature-dependence of the lithium coordination and aggregation of ions might give further insight, if the ionicity interpretation can be related to the observed T-dependence. Other rationalizations of the ionicity, apart from the degree of unpaired ions, are for instance charge transfer form anion to cation [66] or different diffusional states [67]. For pure ionic liquids, the deviation between experimental and Nernst-Einstein conductivity is frequently interpreted by velocity anti-correlations between the different ions [51].…”
Section: Self-diffusion Coefficientsmentioning
confidence: 99%
“…Further investigations on the temperature-dependence of the lithium coordination and aggregation of ions might give further insight, if the ionicity interpretation can be related to the observed T-dependence. Other rationalizations of the ionicity, apart from the degree of unpaired ions, are for instance charge transfer form anion to cation [66] or different diffusional states [67]. For pure ionic liquids, the deviation between experimental and Nernst-Einstein conductivity is frequently interpreted by velocity anti-correlations between the different ions [51].…”
Section: Self-diffusion Coefficientsmentioning
confidence: 99%
“…For diffusion to occur, the ion must ‘jump’ from this cage to a neighbouring cage. 50 – 52 It is this jump that provides a high activation barrier to translation, thus leading to slow diffusion of ions in ionic liquids. In their study of the size, shape, and charge of a solute rotating in [C 4 C 1 im][BF 4 ] Rumble et al demonstrated that such diffusive jumps were much more common and of greater amplitude for the smaller probes, where they significantly contributed to rotational diffusion coefficients, but rarer in the case of larger probes.…”
Section: Resultsmentioning
confidence: 99%
“…[126] The velocity of translocation of analytes is likely to be coupled with the clustering of ions. [128] However, the understanding of these processes are still in the nascent stage. [43] So far, it is relatively well accepted that for the majority of ILs, the cation is more diffusive than the anion.…”
Section: Transport In the Il-filled Porementioning
confidence: 99%
“…[ 126 ] The velocity of translocation of analytes is likely to be coupled with the clustering of ions. [ 128 ] However, the understanding of these processes are still in the nascent stage. [ 43 ]…”
Section: Interaction Of Neat Ils With Nanoporesmentioning
confidence: 99%